Pemberdayaan Perempuan Pengrajin Genteng Di Desa Ngembalrejo Kabupaten Kudus: Upaya Di Tengah Marjinalisasi dan Eksploitasi - Siti Malaiha Dewi; M. Amin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
Ideally, women who spend time and energy in the workplace are directly proportional to the high quality of life. However, this is not the case with tile craftsmen in the circle of the Holy IAIN campus. Women tile craftsmen have no job certainty, guaranteed work safhety, and high health risks. There is no certainty about work because it is only employed during the dry season, while in the rainy season it is idle. However, this condition continues because there are no other job choices. Therefore, life skill training in the manufacture of pastries, wet cakes, and application trays as alternatif businesses is expected to answer the uncertainty of work so far. This activity was attended by 20 women tile craftsmen with direct practice methods, then training in family financial management. As a result, female tile craftsmen have alternatif skills so that no more women are unemployed when the rainy season arrives, so they can increase their income and confidence. In addition, a women's association of tile craftsmen was successfully established as a place to share and mutually reinforce women among tile craftsme.